Cultural Consumption as a Trait of a Sustainable Lifestyle: Evidence from the European Union - Vegheș, Călin (European Journal of Sustainable Development, 2020)
At a first sight, the consumption of cultural goods, services, events, and activities is expected to improve significantly the individual’s wellbeing and quality of life and, reciprocally, overall good quality of life should stimulate the cultural access, participation, and consumption. First evidence that things could stay differently comes from the European Union where, paradoxically, the relatively high overall quality of life does not correspond to a similar level of cultural access, participation, and consumption. Are there significant connections between the consumption of cultural goods, services, events, and activities and the overall quality of life? Does cultural consumption contribute to a sound improvement of the individual’s quality of life? May cultural consumption be defined as a trait of a sustainable lifestyle? These are the main questions this paper aims to answer based on the secondary data regarding cultural access, participation, and consumption, and quality of life at the level of the European Union. Keywords: Cultural consumption, quality of life, sustainable development